Some constraints on the modelling using the uranium isotopes 238U and 234U for dating groundwaters from Guarany aquifer, South America - Bonotto, Daniel Marcos [UNESP] (2000)
Groundwaters from the Guarany aquifer located at the South American continent and sampled at four wells with described geological sections in São Paulo State, Brazil, were chemically and isotopically analysed with two aims: to evaluate the quality of this important hydrological resource and to investigate the possibility of using the natural uranium isotopes 234U and 238U as a chronological tool, since the 234U/238U activity ratio and dissolved U content data in groundwater systems have generated models for dating purposes.